Konsepsi Islam Tentang Manusia Dan Implikasinya Pada Pendidikan - Khairuddin Khairuddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
God affirms that man is at the top of his creation, with a degree of perfection and uniqueness that is superior to all other creatures. (QS.At-Tin:4). But God warned him that he was not yet perfected and that he had to struggle to be perfected. (QS.Asy-Syams:7-10). This perfecting process is possible because the human being is in essence philosophical, intellectual, and intelligent, plus the coming of the apostles of the Lord, bringing the Scriptures as guidance to mankind's life. (QS.An-Nisa:174). It will not be accomplished if man does not use his understanding and does not follow the guidance of God. Education is simply a process of humanizing man;